Introduction to sustainable development leadership and strategies in higher education - Sengupta, Enakshi; Blessinger, Patrick; Yamin, Taisir Subhi (Bingley, U.K. : Emerald Publishing Limited, 2020)
The world's leading international agencies are promoting and stimulating the intellectual debate towards incorporating sustainability in main stream education with the help of thought leaders. This volume highlights innovative pedagogy, discusses the learning methods which can help us to address the world's current sustainability challenges, and offers solutions to meet these. The case studies featured, offering international insight from Malaysia to Australia, discuss curriculum development and integrating sustainability within the core philosophy of the university. The authors explore how leadership education needs to innovate to effectively respond to current sustainability challenges. This topical volume contextualizes the heightened interest in sustainable education across the globe and will be of interest to researchers, university leaders, and students interested in a sustainable future for universities and society as a whole.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Sustainable development; Sustainable development -- Study and teaching (Higher); Business & Economics -- Development -- Sustainable Development; Environmental economics